Revolutionizing Sustainability Education : Stories and Tools of Mindset Transformation - Ivanova, Ekaterina, editor 645694; Rimanoczy, Isabel, 1956-, editor 636175; Taylor & Francis Group (Online service) 645650 (Abingdon, Oxon : Routledge, 2022)
"There is growing awareness among leading responsible management scholars and practitioners that understanding global wicked problems is insufficient in effecting lasting engagement and changed behaviors. Research indicates that to impact behavior, the mindset has to shift, which leaves the question: How do you shift a mindset? This book guides educators and practitioners, their students and colleagues for taking action on finding urgent solutions for the grand challenges stated in the 17 UN Sustainable Development Goals. A Sustainability Mindset is a way of thinking and being that results from a broad understanding of the ecosystem, from social sensitivity, and an introspective focus on our personal values and higher self, which finds its expression in actions for the greater good. By promoting a mindset shift, educators in very diverse contexts are laying the foundation for a resilient future. The book presents a collection of over 150 student voices depicting a transformative experience and shift in their mindset. Seventeen educator/student teams of contributing authors from across five continents describe in the activity that prompted those students' reflections, and the conceptual frameworks that played a role in the selection of the learning goals and activities. The book is written with academic and corporate educators, reflective practitioners, consultants, coaches, trainers and students in mind, and is invaluable in guiding the process of developing a sustainability mindset amongst participants in the training process"-- Provided by publisher.